Challenges of vaccination and herd immunity in COVID‐19 and management strategies. (29th September 2022) - She, Jun; Hou, Dongni; Chen, Cuicui; Bi, Jing; Song, Yuanlin
Abstract: Coronavirus disease 2019 (COVID‐19), the highly contagious viral disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has spread worldwide with millions of cases and more than 5 million deaths to date. SARS‐CoV‐2 has caused serious damage all over the world with many countries experiencing the third or the fourth wave of the viral disease outbreaks, mainly due to the emergence of mutant variants. Those who unvaccinated remain most vulnerable to COVID‐19 and its variants. COVID‐19 vaccination, along with prevention strategies, is a critical measure to defense against the disease. COVID‐19 vaccination can reduce the spread of virus and help protect susceptible population. Although herd immunity might not be realized solely by vaccination, COVID‐19 vaccines have been proved to be effective in reducing the risk of severe disease, hospitalization, and even death. It is recommended that people get vaccinated as soon as they are eligible. This review summarizes the recent SARS‐CoV‐2 variants that brought challenges for vaccination and herd immunity and discusses promising management strategies. Abstract : A. Vaccination induces production of protective antibodies to block the receptor binding domain (RBD) of spike protein from binding to the host angiotensin‐converting enzyme‐2 (ACE‐2) receptor; B. Mass vaccination in population establishes immune barrier, while no vaccination or few vaccination is at risk of COVID‐19 spreading.